Epidemiological overview of Leprosy, neglected tropical disease that plagues northeast Brazil (Research, Society and Development, 2022)
Neglected diseases constitute a set of diseases that not only prevail in conditions of poverty but contribute to the maintenance of inequality in the country. The objective was to present epidemiological data on leprosy in Northeastern Brazil, dealing with key issues of the disease in the region, such as gender, education and others; in order to assist in the improvement and planning of strategies to fight the spread of the infection in Brazil. This is an observational, retrospective, quantitative and descriptive study of confirmed and notified cases of leprosy in the Northeast region of Brazil, from 2011 to 2020. The analysis of data available in the TABNET/DATASUS system from 2011 to 2020 were confirmed and 121,606 new cases of leprosy were reported in the Northeast region of Brazil, being the region with the highest number of cases in the country. The number of leprosy in the Northeast region was 285,570 cases, it was found that this region is responsible for almost half of the total number of cases of the disease in Brazil (43%). Despite actions taken with the aim of minimizing leprosy as a public health problem in the country, the unequal distribution of this disease that persists and demonstrates a reality of lack of equity in the National Health System. The need for programs aimed at health care and guidance to the population regarding this neglected infection and surrounded by discrimination is evident.